Pengaruh Ekspor dan Impor Terhadap Cadangan Devisa di Indonesia Tahun 2020-2024 - Mely Hantari; Azriel Dani Danuarta; Ahmad Surya Hadinata (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study describes the fluctuating exports and imports over the past five years, from 2020 to 2024, which also influenced fluctuations in Indonesia's foreign exchange reserves. The purpose of this study is to determine the effect of exports and imports on Indonesia's foreign exchange reserves from 2020 to 2024. The research method is quantitative using secondary data obtained from the Indonesian Central Bureau of Statistics. The population in this study was 5 years from 2020 to 2024. Data analysis used classical assumption tests consisting of normality tests, multicollinearity tests, and heteroscedasticity tests. In addition, hypothesis tests were also used, consisting of partial tests, simultaneous tests, and coefficient of determination tests. The results of this study indicate that the export variable has a negative effect on Indonesia's foreign exchange reserves from 2020 to 2024. The import variable has a positive effect on Indonesia's foreign exchange reserves from 2020 to 2024. Export and import variables do not simultaneously affect Indonesia's foreign exchange reserves from 2020 to 2024. The implication of this research is that the government needs to manage export and import policies more effectively, as they do not always have the theoretical impact on foreign exchange reserves. Improvements in export quality and import controls are needed, as well as consideration of other factors such as foreign investment and economic policies to maintain the stability of foreign exchange reserves.